Avifaunal Community Composition and Current Status in Basai Wetlands: An Important Bird Area in Haryana, India - Rai, Deepak; Gulia, Rakesh; Chopra, Girish; Kumar, Parmesh (Indian Forester, 2019)
Basai wetlands-an Important Bird Area (IBA site) in Haryana, India, is a potential wintering site for migratory birds from the Palearctic region. Field surveys were conducted from October 2015 to September 2017, following line-transects method together with opportunistic observations to assess assemblage of avifauna in this IBA site. A total of 171 avian species belonging to 51 families and 17 orders were recorded, of which 101 were residents, 62 were winter migrants and 8 were summer migrants. Anatidae was the most diverse avian family. Species richness (104 species in 2016, and 98 species in 2017) was recorded to be highest in the month of January. Eight species are considered as Near Threatened, four species as Vulnerable, two species as Endangered and one species as Critically Endangered in IUCN Red List. Ten species having a globally declining population trends, are frequently seen in the study area. This reveals that the study area is a potential habitat for bird species of conservation priorities. Habitat alteration, weed infestation, water scarcity, discharge of untreated domestic sewage and industrial effluents remained as the major threats to the avifauna. Regular and long-term monitoring of avifauna is an excellent means of keeping watch on ecosystem health and thus might be useful to foster its sustainable improvement.